2015
DOI: 10.4238/2015.february.6.11
|View full text |Cite
|
Sign up to set email alerts
|

Association between the CYP1A1 polymorphisms and hepatocellular carcinoma: a meta-analysis

Abstract: ABSTRACT. Numerous studies have evaluated the association between CYP1A1 gene polymorphisms and hepatocellular carcinoma (HCC) risk. However, the specific association is still controversial. The aim of our study was to clarify the effects of CYP1A1 gene polymorphisms (3801 T>C and A2455G) on HCC risk by conducting a meta-analysis. We conducted searches of the literature published in PubMed and EMBASE databases up to April 2014. We estimated the pooled odds ratio with its 95% confidence interval to assess the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…1 ). Indeed, different studies have shown the association of Cyp1A1 polymorphisms with the risk of developing breast [43] , liver [44] , and lung [ 45 , 46 ], and Tomcod [47] cancers. Studies in humans suggest that variations in CYP1A1 cDNA influences the genetic susceptibility to neoplasia [48] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Indeed, different studies have shown the association of Cyp1A1 polymorphisms with the risk of developing breast [43] , liver [44] , and lung [ 45 , 46 ], and Tomcod [47] cancers. Studies in humans suggest that variations in CYP1A1 cDNA influences the genetic susceptibility to neoplasia [48] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the inhibition of CYP1A1 expression by GNMT may suppress the development of tumors associated with Cyp1A polymorphism. PREX2 is a regulator of the small guanosine triphosphatase Rac, that inhibits PTEN (Phosphatase and tensin homolog) activity, thus upregulating the PI3K/AKT signaling pathway [ 43 , 44 , 49 ]. Different studies decribed the beneficial therapeutic effect of PI3K/AKT inhibitors especially if associated with RAS/MEK/ERK inhibitors [49] .…”
Section: Discussionmentioning
confidence: 99%
“…Gene polymorphism in GSTM1, GSTT1, GSTP1, CYP1A1 and CYP2E1 represent risk-modifying factors for ethanol related diseases in Brazilian alcoholics and controls with similar ethnic backgrounds. Also the persons with these genotypes are genetically more prone to the development of alcoholic pancreatitis and alcoholic cirrhosis, respectively [60][61][62][63].…”
Section: Genetic Polymorphism In Cyp2e1mentioning
confidence: 99%
“…To investigate whether GSTM1, GSTT1, GSTP1, CYP1A1 and CYP2E1 gene polymorphisms represent risk-modifying factors for ethanol related diseases, a study was conducted involving Brazilian alcoholics and controls with similar ethnic backgrounds (Burim et al, 2004). Results were indicating that persons with these genotypes are genetically more prone to the development of alcoholic pancreatitis and alcoholic cirrhosis, respectively (Lakkakula et al, 2013;Yu et al, 2015).…”
Section: Genetic Polymorphismmentioning
confidence: 99%